2003
DOI: 10.1086/378204
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Cutaneous Leishmaniasis in Northern Israel

Abstract: This study describes a new focus of cutaneous leishmaniasis (CL) due to Leishmania tropica, in the Galilee region of northern Israel. Thirty-three cases from 4 villages (northern part) and from the city of Tiberias (southern part) have been clinically diagnosed since 1996. Parasites from 13 patients and from 6 sand flies were characterized by isoenzyme electrophoresis, 2 immunological methods, and 3 polymerase chain reaction (PCR)-based methods. Isolates from the northern part were antigenically similar to Lei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
117
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 35 publications
4
117
1
2
Order By: Relevance
“…The two were far from the only known small foci of Southeast. The clinical picture of confirmed cases was similar to those described for lesions caused by L. tropica in Middle East: ulcerating dry lesion often on the face or on upper extremities that generally last a long time before healing and are difficult to treat (Jacobson et al, 2003). Data on parasite isolates indicate a similarity with L. killicki known in the Tunisian foci and no heterogeneity was found.…”
Section: Discussionsupporting
confidence: 65%
“…The two were far from the only known small foci of Southeast. The clinical picture of confirmed cases was similar to those described for lesions caused by L. tropica in Middle East: ulcerating dry lesion often on the face or on upper extremities that generally last a long time before healing and are difficult to treat (Jacobson et al, 2003). Data on parasite isolates indicate a similarity with L. killicki known in the Tunisian foci and no heterogeneity was found.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies in northern and central Israeli L. tropica rural foci showed that 10-13% of the hyraxes tested by ITS1 PCR were positive for parasite DNA. 7,25 This is approximately half the value found (23.5%) in this study using the same assay. In addition to the ITS1 PCR, we used a highly sensitive kDNA realtime PCR to obtain a more accurate value for the prevalence of L. tropica infection in hyraxes and compared it with ITS1 PCR.…”
Section: Discussionsupporting
confidence: 53%
“…7,12 In other studies, laboratory diagnosis of infection was achieved mostly by testing dermal biopsies, both in humans and in hyraxes. 7,25,29 The presence of L. tropica DNA in hyrax blood shown in the current study could be due to the circulation of live amastigotes present in phagocytes or to degraded parasites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations